Design Transactions Rethinking Information Modelling for a New Material Age - Sheil, Bob; Thomsen, Mette Ramsgaard; Tamke, Martin; Hanna, Sean (UCL Press, 2020)
Design Transactions presents the outcome of new research to emerge from 'Innochain', a consortium of six leading European architectural and engineering-focused institutions and their industry partners. The book presents new advances in digital design tooling that challenge established building cultures and systems. It offers new sustainable and materially smart design solutions with a strong focus on changing the way the industry thinks, designs, and builds our physical environment. Divided into sections exploring communication, simulation and materialisation, Design Transactions explores digital and physical prototyping and testing that challenges the traditional linear construction methods of incremental refinement. This novel research investigates 'the digital chain' between phases as an opportunity for extended interdisciplinary design collaboration. The highly illustrated book features work from 15 early-stage researchers alongside chapters from world-leading industry collaborators and academics.